Analisis Kebutuhan Sistem Informasi Pembelajaran Daring pada Lab Bank Syariah Politeknik Negeri Bandung - Diharpi Herli Setyowati; Hasbi Assidiki Mauluddi; Dimas Sumitra Danisworo; Djoko Cahyo Utomo Lieharyani (Journal of Applied Islamic Economics and Finance, 2021)
The main purpose of this study is to analyze the needs for the development of Islamic Bank Lab learning media. in Politeknik Negeri Bandung. The stages of research on needs analysis of teaching media development carried out were: data collection, data analysis and document review, identification of actors, and making use case diagrams. The analysis was carried out on the current system using PIECES analysis. The results of the PIECES analysis are made in tabular form. In addition, a functional and non-functional requirements analysis was also carried out. Identification of actors who will play a role in teaching media is described in the form of use case diagrams. The results of the PIECES analysis show that a system is needed that can accommodate practical learning in the lab. Islamic banks that can be accessed by students from anywhere in real time, fast and easy to use by all actors involved. Therefore, it is necessary to develop an information system as a learning medium in the Islamic Bank lab. Politeknik Negeri Bandung.